Borate Deposits of Turkey and Argentina: A Summary and Geological Comparison - Helvaci, Cahit (2000)
Turkey has the largest borate reserves in the world and Argentina is in third place. Both countries have calcium and sodium borate deposits where colemanite, ulexite and borax are the principal minerals. We present here a comparison of the main borate deposits interlayered in continental Miocene volcaniclastic rocks of the Anatolian plateau (Turkey) and those of the Puna high plateau (Argentina). The main borate deposits of Turkey are at Emet, Bigadiç, Kestelek and K›rka. Emet is in the western part of the Kütahya province. In Emet, a sedimentary lacustrine sequence rich in tuffaceous materials hosts the colemanite section. There are limestones and marl layers at the base and top of the borate section. Arsenic minerals (realgar and orpiment) are very abundant and spatially related to the borates, indicating a common genetic origin. The principal borate mineral is colemanite with minor ulexite, hydroboracite, meyerhofferite, and rarer species such as veatchite-A, tunellite, teruggite and cahnite. Colemanite occurs as nodules of different sizes, agglomerated in thick beds. Bigadiç has borates interbedded with tuffs, clay and limestone layers. The borate minerals are formed in two distinct zones, lower and upper, separated by thick tuff beds. Colemanite and ulexite predominate in both borate zones. Other borates include howlite, probertite and hydroboracite in the lower zone, and inyoite, meyerhofferite, pandermite (priceite), terschite, hydroboracite, howlite, tunellite and rivadavite in the upper borate zone. The Kestelek deposit is 27 km southeast of the town of Mustafa Kemalpafla in the province of Bursa. The borate zone consists of marl, limestone, tuffaceous limestone, tuff and borate layers. The borate minerals occur interbedded with clay minerals. Colemanite is present as masses from nodule to boulder size (up to 1 m in diameter), and as thin layers of fibrous and euhedral crystals. Colemanite, ulexite and probertite predominate and sparse hydroboracite is also present locally. The K›rka stratigraphic succession comprises borates that are intimately interbedded with and penetrating marls, claystones, zeolitized tuff and tuffaceous epiclastic material in the lacustrine sedimentary rocks. The main boron mineral is borax with lesser amounts of colemanite, ulexite and other borate minerals. The volcano-sedimentary rock units in the Sultançay›r deposit include borate-bearing gypsum intercalated in a sandy claystone unit. Calcium borates, mainly pandermite (priceite) and howlite, but also colemanite and bakerite, are interspersed within the Sultançay›r gypsum. The borates in all of these districts occur in older playa lake deposits of Miocene age that rest unconformably on a Paleozoic and Mesozoic basement that is comprised of ophiolites, marbles and schists. Argentina has lacustrine borate deposits restricted to 1) Sijes hill in the Los Andes districts of the Salta province, 2) the Loma Blanca deposits of the Jujuy province and 3) the Tincalayu deposit located on the northwestern margin of the Hombre Muerto Salar. There are also several borate occurrences within salars of the Andes region. Sijes hill is a topographically positive area of Miocene rocks, 30 km long, along the eastern border of the Pastos Grandes salt pan. Borates occur as interbeds in a very thick lacustrine volcaniclastic sequence. Several evaporitic members, with halite at the bottom and borate and gypsum at the middle and top, are interlayered with tuffs and tuffaceous materials. Colemanite is the main borate mineral at the Monte Verde, Esperanza and Santa Rosa mines. Other deposits are composed principally of mainly hydroboracite, the principal borate mineral in the Sijes district. Colemanite occurs as spherules agglomerated in beds less than 1 m thick and is accompanied by hydroboracite, inyoite and ulexite. Predominantly borax and trace amounts of colemanite, ulexite and other borate minerals are also present in the Loma Blanca deposit of the Jujuy province, and in the Tincalayu deposit.